Implementation of The “Little Detective”: Structured Stimulation Programme to Improve Problem Solving Skills in Early Chilhood - Euis Trismayanti; Ati Nuriah; Atih Syaidah; Mira Sofatul Ma’la (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This research is motivated by the low problem-solving abilities of early childhood children in Kober Cerdas Ceria 2, which is indicated by the high dependence of children on teachers and parents when facing simple problems. This research aims to improve children's problem-solving abilities through the "Little Detective" program with a structured stimulation method. The type of research used is Classroom Action Research (CAR) which is implemented in three cycles. The research subjects were 18 children in group A of Kober Cerdas Ceria 2, consisting of 9 boys and 9 girls. Data collection techniques were carried out through observation, interviews, and documentation. The "Little Detective" program was implemented through various structured stimulation activities such as collage, puzzles, role play, grouping objects, and cutting and pasting activities. The results of the study showed an increase in children's problem-solving abilities in each cycle. In the pre-cycle, most children were in the Undeveloped category (72.22%). In cycle I, the Developing According to Expectations category began to emerge at 11.11%. Then in cycle II, the Developing Very Well category reached 16.66%, and increased significantly in cycle III to 72.22%. Thus, the "Little Detective" program through structured stimulation methods is effective in improving the problem-solving abilities of early childhood in Kober Cerdas Ceria 2